Christology and evil in Ghana : towards a Pentecostal public theology - Quayesi-Amakye, Joseph. (Currents of Encounter, 2013)
Pentecostalism has traditionally always been other-worldly in the sense that Pentecostals tend to believe that people's lives are controlled by unseen powers that are responsible for both good and bad. This makes people look for a power that is stronger than those of evil and can ensure that believers enjoy good health and prosperity. Pentecostals find this power in Jesus Christ, who is victorious over all evil powers, and therefore pray that Jesus will save them. For them, life is characterised by suffering and evil, but in Christ they are conquerors, and life is full of concrete blessings. Using songs and sermons, this book shows the main widespread beliefs of the leadership and grassroots members of the Church of Pentecost (Ghanaian Pentecostals) on Christology and evil. It discusses their fear of evil and their finding solace in the power of Jesus. The author supplements this attitude by the biblical calling to help build a just and peaceful society. He thus develops a theology of the public domain in which the church can make a difference by developing its diaconal services, establishing more educational institutions, and helping-together with people who want to collaborate-build a just and more affluent society with good healthcare and a literate and thriving population. This book balances on the interface between traditional African religious ideas and practices and Christian ideals for a more humane society.